Attachment loss attributable to third molar malposition/extraction: Case classification - Joseph Jankovich, DMD (Elsevier, 2024)
OBJECTIVES: The 2017 World Workshop on the Classification of Periodontal and Peri-implant Diseases and Conditions established a periodontitis staging and grading scheme that-for the first time-integrates an assessment of disease severity with an appraisal of therapeutic complexity and risk for disease progression. Individuals exhibiting attachment loss attributable to third molar malposition or extraction represent a large cohort of non-periodontitis patients highly likely to respond favorably to treatment. The purpose of this clinical report is to illustrate the value in formally categorizing this common periodontal condition. METHODS: Two male patients were referred to the Department of Periodontics, Army Postgraduate Dental School, for evaluation of bone and attachment loss limited to distal surfaces of mandibular second molars. Each patient was treated using a combination of guided tissue regeneration and bone replacement grafts. RESULTS: Favorable clinical and radiographic outcomes were observed over follow-up periods ranging from 4 months to 4 years. CONCLUSIONS: Treatment outcomes following regenerative periodontal procedures depend in part on patient-related factors. Periodontal defects attributable to anatomic, developmental, and iatrogenic factors in nonperiodontitis patients may respond favorably to therapy with high reliability. IMPLICATIONS: Many patients experiencing bone and attachment loss attributable to third molar malposition or extraction lack periodontitis risk factors/indicators, have low susceptibility to the disease, and are highly likely to respond favorably to treatment. Future classification systems of periodontal diseases and conditions should formally categorize this commonly encountered periodontal condition.